2015
DOI: 10.2527/jas.2014-8567
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal energy status during midgestation on beef offspring carcass characteristics and meat quality1

Abstract: Research has suggested that maternal undernutrition may cause the development of a thrifty phenotype in the offspring, potentially resulting in greater adiposity and reduced muscle mass. These alterations in adipose and muscle development could have lasting impacts on offspring growth, carcass characteristics, and meat quality. However, limited research exists evaluating the impact of maternal energy status on these economically important traits of the offspring. Therefore, the objective of this study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
30
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 24 publications
10
30
0
5
Order By: Relevance
“…In beef cattle, feeding cows at 80% requirements between 3 and 6 months of gestation reduced subcutaneous rib fat thickness and increased the intra-to inter-muscular fat ratio in 7 months old calves (Mohrhauser et al, 2015). The birthweight of calves born to Angus cross-bred cows fed 60% of their requirements between 30 and 85 days or between 30 and 140 days of gestation was the same as offspring born to cows fed 100% of requirements but their liver was heavier (Prezotto et al, 2016).…”
Section: Undernutritionmentioning
confidence: 61%
“…In beef cattle, feeding cows at 80% requirements between 3 and 6 months of gestation reduced subcutaneous rib fat thickness and increased the intra-to inter-muscular fat ratio in 7 months old calves (Mohrhauser et al, 2015). The birthweight of calves born to Angus cross-bred cows fed 60% of their requirements between 30 and 85 days or between 30 and 140 days of gestation was the same as offspring born to cows fed 100% of requirements but their liver was heavier (Prezotto et al, 2016).…”
Section: Undernutritionmentioning
confidence: 61%
“…Además, se ha observado que la restricción de nutrientes durante la gestación en vacas Angus cruza afecta los metabolitos maternos y el crecimiento fetal (Taylor et al, 2018). Sin embargo, la restricción de nutrientes no alteró el peso del útero, el peso de los placentomas o el peso de las carúnculas, pero aumentó el peso del cotiledón y el área total de la superficie de los placentomas en vacas con restricción de nutrientes en gestación temprana o media (Taylor et al, 2015). Debido a que la gestación temprana es un período crítico del desarrollo de tejidos y órganos fetales, se ha observado que la nutrición materna induce RCIU durante este período.…”
Section: Impacto De La Restricción De Nutrientes Específica Para El Gunclassified
“…Lo que refuerza aún más la idea de que los miARN funcionales son necesarios para el desarrollo fetal adecuado. Recientemente, los perfiles de miARN de placentomas de vacas con restricción de nutrientes durante la gestación temprana presentaron una mayor alteración en la abundancia de miARN y vías enriquecidas asociadas con la guía de axones, endocitosis, interacción ligando-receptor neuroactivo y vía de señalización MAPK (Taylor et al, 2015). Esto se vio respaldado por los perfiles de miARN circulantes en los que las vacas con restricción de nutrientes durante la gestación temprana y media presentaron abundancia de alteraciones de miARN independientemente del momento en que se indujo la carencia nutricional, así como el enriquecimiento de la vía de genes objetivos como: vías en el cáncer, AMPc señalización, adhesión focal, señalización Ras, proteoglicanos en cáncer y vías de señalización MAPK (McCarty et al, 2019).…”
Section: Microarnunclassified
See 1 more Smart Citation
“…Currently, evaluations of the meat quality of livestock have revealed that the content of intramuscular fat (IMF) is lower in carcass fats, yet IMF has a critically 4 important influence on the edibility and flavor of muscle meat [1]. Indeed, the quantity of IMF has become one of the most critical parameters in meat quality indicators, as it is considered to be positively related to meat quality and texture [2,3]. When a certain amount of fat is deposited between the muscle bundles and muscle fibers, the marbled section of the meat has a high score, and the meat is fresh and juicy, which is often considered ideal [4, 5].…”
mentioning
confidence: 99%